Coumarin Reduces Virulence and Biofilm Formation in Pseudomonas aeruginosa by Affecting Quorum Sensing, Type III Secretion and C-di-GMP Levels - Zhang, Yunhui; Sass, Andrea; Van Acker, Heleen; Wille, Jasper; Verhasselt, Bruno; Van Nieuwerburgh, Filip; Kaever, Volkhard; Crabbé, Aurélie; Coenye, Tom (Frontiers in Microbiology, 2018)
As one of the major pathogens in wound infections, Pseudomonas aeruginosa produces several virulence factors and forms biofilms; these processes are under the regulation of various quorum sensing (QS) systems. Therefore, QS has been regarded as a promising target to treat P. aeruginosa infections. In the present study, we evaluated the effect of the plant-derived QS inhibitor coumarin on P. aeruginosa biofilms and virulence. Coumarin inhibited QS in the P. aeruginosa QSIS2 biosensor strain, reduced protease and pyocyanin production in different P. aeruginosa strains, inhibited biofilm formation both in microtiter plates and in an in vitro wound model, and reduced P. aeruginosa virulence in the Lucilia sericata infection model. Transcriptome analysis revealed that several key genes involved in the las, rhl, Pseudomonas quinolone signal (PQS) and integrated quorum sensing (IQS) systems were down-regulated in the coumarin-treated biofilm of P. aeruginosa PAO1. Coumarin also changed the expression of genes related to type III secretion and cyclic diguanylate (c-di-GMP) metabolism. The cellular c-di-GMP level of P. aeruginosa PAO1 was significantly reduced by coumarin. These results provide new evidences for the possible application of coumarin as an anti-biofilm and anti-virulence agent against P. aeruginosa in wound infections.